2003
DOI: 10.1093/jxb/erg009
|View full text |Cite
|
Sign up to set email alerts
|

Increased growth of young citrus trees under reduced radiation load in a semi-arid climate1

Abstract: This study investigated the effects of radiation heat-load reduction by shading on the growth and development of citrus trees in a warm subtropical region. The experiment was conducted from mid-June until late October when daily maximal air temperature averaged 29.3 degrees C. Two-year-old de-fruited Murcott tangor (Citrus reticulata BlancoxCitrus sinensis (L.) Osb.) trees were grown under 30% or 60% shade tunnels, or 60% flat shade (providing midday shade only), using highly reflective aluminized nets. Non-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
36
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 21 publications
7
36
0
11
Order By: Relevance
“…To overcome the problem of dormancy, several treatments including chilling, heating, soaking, washing, adding gibberellic acid GA 3 (Ekpong 2009), stratification, changing photoperiod, temperature, and storage time (Raboteaux and Anderson 2010) have been attempted in Cleome seeds. Seeds of C. gynandra from fresh intact pods were sown directly (without standard sterilization) onto sterile Petri dishes with wet filter papers, resulting in high rates (80-90%) of seed germination (Newell et al 2010). In this study, fresh collection of seeds from C. spinosa, standard sterilization, chilling, and photoperiod, as described in ''Materials and methods'', were crucial to achieving high rates of seed germination (more than 90% were regularly obtained) and low levels of contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the problem of dormancy, several treatments including chilling, heating, soaking, washing, adding gibberellic acid GA 3 (Ekpong 2009), stratification, changing photoperiod, temperature, and storage time (Raboteaux and Anderson 2010) have been attempted in Cleome seeds. Seeds of C. gynandra from fresh intact pods were sown directly (without standard sterilization) onto sterile Petri dishes with wet filter papers, resulting in high rates (80-90%) of seed germination (Newell et al 2010). In this study, fresh collection of seeds from C. spinosa, standard sterilization, chilling, and photoperiod, as described in ''Materials and methods'', were crucial to achieving high rates of seed germination (more than 90% were regularly obtained) and low levels of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Since transformation of C. gynandra (a C 4 plant in the genus Cleome) has been reported recently (Newell et al 2010), our protocol will facilitate the functional comparison between C 3 plant C. spinosa and C 4 plant C. gynandra using transgenic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, recent evidence has demonstrated that light is also the main factor triggering the transition between vegetative to reproductive developmental stages of trees in Equatorial regions (Borchert et al, 2005). The effects of light on developmental processes in citrus and other neotropical tree species have been described in several situations, although without approaching the molecular aspects of the metabolism (Steppe et al, 2006;Chen L-S et al, 2005;Raveh et al, 2003;Torné et al, 2001). Mutant studies employing transgenically generated plants have demonstrated variable extents of functional conservation in the genes responsible for developmental control between citrus and model species (Pena et al, 2001;Pillitteri et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The use of protective netting in fruit tree cultivation is an effective method of preventing yield loss that can result from high temperatures and irradiation, strong wind, and hail (Manja and Aoun, 2019;Mupambi et al, 2018;Raveh et al, 2003;Stamps, 2009;Wachsmann et al, 2014). Often, the use of protective netting also results in changes in the orchard microclimate that can alter tree physiology and improve tree performance and fruit development (Cohen et al, 2005;Manja and Aoun, 2019;Mupambi et al, 2018;P erez et al, 2006;Raveh et al, 2003;Stamps, 2009;Wachsmann et al, 2014;Zhou et al, 2018). Various different types of permanent protective netting structures and/ or different colors of shade netting have been tested to determine their effects on tree physiology and fruit development and quality (Manja and Aoun, 2019;Mupambi et al, 2018;Stamps, 2009;Wachsmann et al, 2014;Zhou et al, 2018).…”
mentioning
confidence: 99%